2015
DOI: 10.1007/s00775-015-1249-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of new salicylaldehyde-2-picolinylhydrazone Schiff base compounds of Ru(II), Rh(III) and Ir(III) as in vitro antitumor, antibacterial and fluorescence imaging agents

Abstract: Reaction of salicylaldehyde-2-picolinylhydrazone (HL) Schiff base ligand with precursor compounds [{(p-cymene)RuCl2}2] 1, [{(C6H6)RuCl2}2] 2, [{Cp*RhCl2}2] 3 and [{Cp*IrCl2}2] 4 yielded the corresponding neutral mononuclear compounds 5-8, respectively. The in vitro antitumor evaluation of the compounds 1-8 against Dalton's ascites lymphoma (DL) cells by fluorescence-based apoptosis study and by their half-maximal inhibitory concentration (IC50) values revealed the high antitumor activity of compounds 3, 4, 5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 56 publications
0
20
0
1
Order By: Relevance
“…In this study, an anti-proliferative effect along with antioxidant capacity of the complexes was observed. (31). Moreover, [Ru2(p-cym) 2 (L) 2 ]X 2 -mediated anticancer effect was also seen against HL-60, A2780, MCF7 and PC3 cell lines at 40 mg/mL or ~600 µM (32).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study, an anti-proliferative effect along with antioxidant capacity of the complexes was observed. (31). Moreover, [Ru2(p-cym) 2 (L) 2 ]X 2 -mediated anticancer effect was also seen against HL-60, A2780, MCF7 and PC3 cell lines at 40 mg/mL or ~600 µM (32).…”
Section: Discussionmentioning
confidence: 88%
“…Scientific reports have suggested that [Ru2(p-cym)2(L)2]X2 complex is the strong cytotoxic agent to cancer cells (32). On the other hand, [{(p-cymene) RuCl2} 2 ] complex was found to act against pathogenic bacteria along with a number of tumor cells (31). By the half-maximal inhibitory concentration (IC 50 ) values and by using fluorescencebased apoptosis study, the in vitro antitumor assessment against Dalton's ascites lymphoma (DL) cells revealed a high antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro analysis on pyrimidine-5-carbonitrile derivatives [53] and on the ruthenium-based complex [(C 6 H 6 )RuL( N , N )Cl] [54] reported antimicrobial activity on S. aureus and other human pathogenic bacteria. In silico studies have identified them as potential Sa TS inhibitors [53,54]; however no experimental evidences have proven their activity towards Sa TS.…”
Section: Inhibitors Of Tss and Fdtss From Human Pathogenic Bacteriamentioning
confidence: 99%
“…Another ruthenium(II) complex with picolinylhydrazone was reported with antibacterial activity with a zone of inhibition around 35 mm on eight bacterial species as well as with high antitumor activity on Dalton's lymphoma (DL) cells versus normal PBMC cells . We have been working for last few years on synthesis of Cp*Rh(III)/ Cp*Ir(III) complexes with various nitrogen donor ligands and their structural and biological studies . According to our knowledge, there is no report available in literature with these metal complexes of pyrimidine ligands (Figure ).…”
Section: Introductionmentioning
confidence: 99%